Bridging Cultural Beliefs and River Restoration Preferences: A Survey of Water Resource Managers in Bali - Nur Aini Iswati Hasanah; Gunawan Suntoro; Asep Yusuf; Bima Anjasmoro (Jurnal Teknik Sumber Daya Air, 2026)
Water, considered as a sacred element in Balinese culture, is deeply connected to the island's spiritual and communal existence. Despite the traditional beliefs of Tri Hita Kirana and Sad Kertih, which emphasize harmony and conservation, the management of Bali's water resources has become increasingly complex due to current issues including pollution. This study addresses connection between the cultural beliefs of Balinese water resource managers and their approaches for addressing current water management challenges, specifically their preference towards river restoration strategies. This study used a quantitative approach to collect data from water resource managers in the Bali Penida River Basin using an online questionnaire via Google Forms. The questionnaire was developed based on two established frameworks to comprehensively explore perceptions of water values, local wisdom, water resources management issues, and the socio-ecological impacts of various river restoration scenarios. The findings show that the perceptions of water of major water resources managers (65%) are influenced by personal experience and cultural heritage, which extend beyond local wisdom alone. Respondents showed a pronounced preference towards combination designs (75% satisfaction) that combine natural components with functional and recreational facilities when considering restoration scenarios. These findings provide policymakers with a practical framework for designing river restoration projects that ensure higher institutional and public compliance by transforming Tri Hita Karana into tangible socio-ecological infrastructure. To achieve sustainable water governance, future river basin regulations must require stakeholder-backed hybrid models rather than isolated ecological restrictions.